Fatty Acids Composition from the Seeds of Crotalaria laburnifolia Linn - Yadava, R.N.; Singh, Abha (Asian Journal of Chemistry, 2010)
Fatty acids composition of Crotalaria laburnifolia Linn seeds has been reported